Sleep, circadian and behavioural characterisation of two schizophrenia-relevant transgenic mouse models - Pritchett, D (2015)
The experiments described in this thesis involved the sleep, circadian and behavioural characterisation of two schizophrenia-relevant transgenic mouse models, both of which are models of altered glutamatergic function. Although schizophrenia cannot be recapitulated in rodents, the study of transgenic mouse models can yield insights into the roles of schizophrenia candidate genes in brain function and dysfunction. D-amino acid oxidase knockout (Dao-/-) mice do not express DAO, a glial peroxisomal enzyme that catalyses the degradation of D-amino acids including D-serine. In turn, D-serine is the primary endogenous co-agonist of the synaptic N-methyl-D-aspartate receptor, an ionotropic glutamate receptor that is strongly implicated in learning and memory, which may be hypoactive in schizophrenia. Given evidence of DAO overactivity in schizophrenia, DAO inhibiting drugs have been proposed as a potential treatment for the disorder. To assess the behavioural consequences of Dao inactivation, Dao-/- mice were subjected to a range of psychiatrically-relevant behavioural tests. Anxiety-like behaviour was increased in Dao-/- mice, while short-term memory performance was enhanced. By contrast, long-term spatial memory acquisition was unaltered in Dao-/- mice. However, the Morris watermaze performance of Dao-/- mice was critically dependent on the radial distance of the hidden platform from the side-wall. Analyses of spatial swimming behaviour revealed that Dao-/- mice demonstrated an increased preference for the periphery of the watermaze arena, which may be another manifestation of heightened anxiety. Prepulse inhibition testing revealed a complex interplay between genotype, sex and stress levels. Likewise, genotype-by-sex interactions were evident in the Morris watermaze and the novelty-suppressed feeding test. Dao-/- mice showed no evidence of sleep or circadian rhythm disruption (SCRD). Taken together, these results suggest that DAO inhibition might ameliorate the memory deficits of schizophrenia patients, although these effects may not extend to long-term associative memory. In addition, these benefits could come at the cost of heightened anxiety. Our data also imply that DAO inhibitors might have different effects in male and female patients. Metabotropic glutamate receptor 2 & 3 double-knockout (Grm2/3-/-) mice lack the inhibitory autoreceptors mGlu2 and mGlu3, which are encoded by the genes Grm2 and Grm3, respectively. Based on the results of genome-wide association studies, Grm3 is amongst the strongest schizophrenia candidate genes. The Grm2/3-/- mouse was used to assess the 'shared neuropathophysiology' hypothesis of SCRD in schizophrenia. This theory posits that the high co-morbidity of schizophrenia and SCRD stems from dysfunction in common brain mechanisms that underpin both pathologies. Consistent with this hypothesis, Grm2/3-/- mice displayed significant SCRD, characterised by reduced sleep duration and increased sleep fragmentation. They also demonstrated increased sensitivity to the circadian effects of light. These data are consistent with the 'shared neuropathophysiology' hypothesis, and tentatively suggest that mGlu3 dysfunction could contribute to SCRD in schizophrenia. Since memory performance is also impaired in Grm2/3-/- mice, this model could be an ideal tool with which to investigate the relationship between sleep disruption and cognitive performance. Finally, Grm2/3-/- mice displayed perturbed wheel-running rhythms under a standard light/dark cycle, despite the fact that their home-cage activity rhythms were unaltered in the absence of a running wheel. Although the basis of this phenotype is unclear, these data speak to the debate about the suitability of running-wheels as a circadian assay for psychiatrically-relevant mouse models.